A perspective on precipitation-hardening high-entropy alloys fabricated by additive manufacturing - Haftlang, Farahnaz; Kim, Hyoung Seop (Materials & design, 2021)
[Display omitted] •A review is presented on recent research on precipitation-hardened high-entropy alloys that can be produced by additive manufacturing.•The different strengthening mechanisms of AMed HEAs were reviewed with emphasis on precipitation strengthening.•The advantages of using applying post-printing heat-treatment for enhancing the strength-ductility relationship of HEAs are discussed.•Dynamic responses of precipitation during deformation are explained through the interaction between dislocations and precipitates.•The future prospects of precipitation-hardened high-entropy alloys fabricated by additive manufacturing are presented. The growing demand for advanced metallic materials with optimum mechanical properties has led to the creation of next-generation materials based on the alloying of multiple-principal elements in high concentrations. High-entropy alloys (HEAs) have a high potential for industrial applications due to their extraordinary properties under elevated, ambient, and cryogenic conditions. Due to several limitations of conventional manufacturing methods, to develop HEAs of the maximum capability, a novel metal additive manufacturing (MAM) technique has been developed to produce defect-free HEA components with the desirable performance. The unique microstructures of MAMed HEAs provide an optimum strength-ductility relationship, even in extreme environments, by the simultaneous activation of several strengthening mechanisms. In particular, applying post-printing heat-treatment can significantly enhance the strength-ductility relationship of HEAs. Herein, a comprehensive review based on the process-microstructure-properties relationship in precipitation-hardenable HEAs fabricated by 3D printing is provided. Different kinds of precipitates formed in the microstructures of MAM-processed HEAs after applying a proper post-MAM heat treatment are presented. Moreover, the corresponding mechanical properties of these components are discussed in detail. Also, the improvement in the mechanical properties of precipitation-hardened MAM-processed HEAs due to the interaction between dislocations and precipitates is introduced, resulting in precipitate shearing and creation of Orowan/Hirsch loops.